congenital syphilis in the state of Espírito Santo - Lima, Lucia Helena M; Gurgel, Maria Fátima C; Moreira-Silva, Sandra F (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: every year, at least half a million infants are born with congenital syphilis, in addition, maternal syphilis causes another half million stillbirthsand miscarriages annually. With the development of reliable and simple tests the disease could be easily detected and treated at little cost. Objectives: todetermine the incidence of congenital syphilis in the last six years in the state of Espírito Santo evaluating antenatal data to optimize preventions and controlmeasures of this disease. Methods: cases of congenital syphilis notified in the STI surveillance system in the state of Espirito Santo in the years of 2000 to2005 were included in this study. The incidence per year per 1.000 lives births and the antenatal care was evaluated. Results: a total of 1803 cases werenotified in this period. The incidence of congenital syphilis from 2000 to 2005 was, respectively of 5.32; 4.94; 5.95; 6.25; 6.13 e 5.08. In 2005, children withcongenital syphilis whose mothers participated in antenatal care corresponded to 75.20%; 78.53% have detected the syphilis during pregnancy and only5.33% of pregnant women have had the adequate treatment. In 60.67% the partner was not treated. Conclusion: in spite of the stability until 2004, weobserved a reduction in the incidence rates of congenital syphilis in 2005. We believe that the strategies results, the health professional training and theimplementation of programs for the reduction of this disease are beginning to show results in the state. We need to improve the antenatal care quality in orderto eliminate this preventable disease from affecting so many children.